1985
DOI: 10.1530/jrf.0.0740335
|View full text |Cite
|
Sign up to set email alerts
|

Semen-induced ovulation in the bactrian camel (Camelus bactrianus)

Abstract: Summary. Bactrian camels (63 \ s=venus\ \ s=venus\ , 8\ s=mar s\ \ s =mar s \ ) were used in the breeding season to determine the factors that will induce ovulation. After insemination of semen samples into the vagina, the ovaries were checked for ovulation by rectal palpation. The results indicated that ovulation was induced by the seminal plasma, but not by the spermatozoa, and the incidence of ovulation after insemination was 87%. Most of the females (66%) had ovulated by 36 h after insemination and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
12

Year Published

1988
1988
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 4 publications
4
68
0
12
Order By: Relevance
“…The scarcity of corpora lutea in the genital tracts of non-pregnant camels can be ascribed to the induced nature of ovulation in this species (Elias et al, 1984;Chen et al, 1985) and the short lifespan of the corpora lutea formed after sterile mating (Fernandez-Baca et al, 1970;Musa & Abusineina, 1978a;Marie & Anouassi, 1987). The progesterone pattern after sterile mating in the camel, in contrast to other farm animals, is characterized by absence of a plateau and early luteolysis (Marie & Anouassi, 1987 (1981).…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of corpora lutea in the genital tracts of non-pregnant camels can be ascribed to the induced nature of ovulation in this species (Elias et al, 1984;Chen et al, 1985) and the short lifespan of the corpora lutea formed after sterile mating (Fernandez-Baca et al, 1970;Musa & Abusineina, 1978a;Marie & Anouassi, 1987). The progesterone pattern after sterile mating in the camel, in contrast to other farm animals, is characterized by absence of a plateau and early luteolysis (Marie & Anouassi, 1987 (1981).…”
Section: Discussionmentioning
confidence: 99%
“…In some earlier studies, it was documented that the sterile copulation with vasectomized males was related with improved LH secretion and a higher ovulation rate in spontaneous ovulators like cattle and sheep (Marion, 1950). Other authors also revealed that ovulation occurred after intravaginal or intramuscular/intrauterine administration (Chen et al, 1985;Pan et al, 1992) of Bactrian SP to female Bactrian camels. Lately, have documented the existence of ovulation-inducing factor (OIF) in seminal plasma of alpacas and llamas that could stimulate a surge in circulation.…”
Section: Role Of Oif Among Speciesmentioning
confidence: 94%
“…It is also acted as a potent stimulator of LH secretion, and has a dose-dependent effect on ovulation rate and CL form and function. Moreover, it acts via a systemic rather than a local pathway, at physiologically relevant doses Chen et al, 1985;Sokol et al, 1985;Izumi et al, 1985;Paolicchi et al 1999).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
See 2 more Smart Citations